Characterization studies for the recovery of land degraded by mining - Longo, R. M.; Ribeiro, A. I. [UNESP]; de Melo, W. J. [UNESP]; Demanboro, A. C.; Bettine, S. C. (WITPRESS LTD., 2012)
The objective of the present work is to evaluate the differences that happened after the tin mining activity in an area of the Amazon forest and establishing planning actions for recovery of the degraded lands. Samples were collected, superficially, along a line with high forest, low forest, plows, reject dry and reject sandy materials. In each situation five samples were collected which worked as repetitions, in a total of 35 samples. In the collected samples physical analyses were accomplished: texture, soil's density and particles and mechanical resistance to penetration and chemical elements: pH (CaCl2); organic matter, P, K, Ca, Mg, Al, CEC and BS. The results showed that the process of tin extraction promoted significant alterations in the soil's properties studied. Parameters such as the organic matter, P, the soil and particle's density were the most altered by the process of suppression of the original vegetation and extraction of the tin. Therefore, when it is intended to implant recovery projects in those areas, the soil's recovery should be prioritised for the success of the enterprise and the different degraded situations should be worked in different ways. © 2011 WIT Press.
Keywords: Amazon forest; Degraded soil; Mining activity